Convention between the United Kingdom of Great Britain and Northern Ireland and the Oriental Republic of Uruguay for the Avoidance of Double Taxation and the Prevention of Fiscal Evasion with respect to Taxes on Income and on Capital, with Protocol. Montevideo, 24 February 2016. ([2017-02-06]) - Unknown
No abstract available